Monocyte to high-density lipoprotein cholesterol ratio as a marker of the presence and progression of diabetic kidney disease - Wentao Yang; Yuanlong Zhong; Pengying Zhou; Donghui Lu (Renal Failure)
Background Monocyte to high-density lipoprotein cholesterol ratio (MHR) is considered a novel marker of inflammation. However, whether MHR can predict the risk of diabetic kidney disease (DKD) remains uncertain. Our research aimed to investigate the relationship between MHR and DKD.Methods This was a cross-sectional retrospective study of 159 participants with type 2 diabetes mellitus. MHR, urinary albumin-to-creatinine ratio (UACR) and other indexes were measured. According to UACR, participants were divided into normal group (UACR < 30 mg/g), moderately increased group (UACR 30-300 mg/g) and severely increased group (UACR > 300 mg/g). The association between MHR and DKD was analyzed.Results MHR was significantly elevated in severely increased albuminuria group (p = 0.029). The prevalence of DKD increased in parallel with the elevation in MHR (p = 0.009). MHR was positively related with DKD in univariate logistic regression analysis (ORs = 11.27, 95%CI 1.26-101.24, p = 0.031). Multivariable logistic regression analysis showed MHR significantly correlated with DKD (ORs = 6.20, 95%CI 1.49-25.84, p = 0.012). Each quartile elevation in MHR was associated with an increased risk of DKD (ORs = 1.90, 95%CI 1.19-3.01, p = 0.007). In subgroup analyses MHR was a risk factor for DKD, particularly in patients with HbA1c <8.0%.Conclusions Our findings suggest that MHR can be used as a marker for the presence and progression of DKD.